Influence of Fibre Treatment on the Characteristics of Buriti and Ramie Polyester Composites. Issue 4 (May 2017) - Lavoratti, Alessandra; Romanzini, Daiane; Amico, Sandro C.; Zattera, Ademir J.
Natural fibres have recently attracted interest due to their beneficial characteristics such as low cost and biodegradability. This work aims to characterise in natura, washed and alkali-treated buriti and ramie fibres and to evaluate the influence of the chemical treatments in the mechanical and dynamic mechanical performances of their composites produced by resin transfer moulding (RTM). Fibres were cut to 45 mm in length, washed in distilled water and treated with 2, 5 and 10 wt.% sodium hydroxide solutions. The chemical composition of the washed fibres was not altered. The 2 wt.% NaOH solution increased the flexural strength of polyester/ramie composites by 70%, and improved the impact performance of the alkali-treated polyester/buriti composites. The polyester/ramie composites exhibited superior dynamic mechanical properties and better adhesion at the fibre/matrix interface, and the morphology of buriti limited the fibre wettability during the RTM processing.